Infant Acute Lymphoblastic Leukemias Are Pan-Sensitive to Obatoclax Across molecular/Cytogenetic Subtypes, Especially MLL-ENL, and gene Expression Profiles Determine Obatoclax IC50: A Report on the Children's Oncology Group (COG) P9407 Trial - Urtishak, Karen A.; Wang, Li-San; Harvey, Richard; Atlas, Susan R; Chen, I-Ming L.; Robinson, Blaine W.; Moukarzel, Lea; Cao, Kajia; Devidas, Meenakshi; Carroll, Andrew J.; Heerema, Nyla A.; Hunger, Stephen; et al. (Blood, 2010)
Abstract 2757 The outcome of infants with acute lymphoblastic leukemia (ALL) remains poor because of the association of frequently occurring MLL translocations with drug resistance and vulnerability of the very young to treatment complications. The two most common MLL partner genes in infant ALL, AF4 (AFF1) and ENL (MLLT1), are associated with particularly poor survival. Better therapies are urgent. One candidate is obatoclax (GeminX Biotechnologies, Inc.), which targets interactions of pan-anti-apoptotic BCL-2 family proteins with BH3 proteins and is now in a Phase I trial for relapsed/refractory pediatric cancers (COG ADVL0816). Previously we showed potent single agent in vitro activity of obatoclax against MLL-rearranged infant ALL (Zhang ASH 2008). Here we evaluate correlations of obatoclax activity with MLL translocation status and gene expression profiles in a large number of cases of infant ALL to define molecular determinants of sensitivity. Bone marrow, peripheral blood or apheresis samples from the time of diagnosis in 54 infants (age 1–365 d, median 168 d; WBC count 15–1230×103/μL, median 445×103/μL) with ALL (n=52) or bilineal acute leukemia (n=2) were examined, 48 of which were from the COG P9407 trial. By molecular/cytogenetic classification, the cases were MLL-AF4+ (n= 28), MLL-ENL+ (n= 11), other MLL rearrangement positive (other MLL+) (n= 8) or MLL germline (MLL-) (n= 7). Single agent IC50 values from MTT assays after 72 h obatoclax exposures were determined in all cases (including 13 previously tested; Zhang ASH 2008) by plotting the surviving fractions. IC50s in the MLL-AF4+ group were compared to those in each of the other 3 molecular/cytogenetic groups by Wilcoxon's test. Gene expression profiling was performed on Affymetrix HG_U133 Plus2.0 arrays in 47 of the 48 COG P9407 cases. Spearman test was used to identify correlation between log2 expression levels for each probeset and IC50 values across subjects. A heatmap of significant probesets (p≤0.001) was generated by transforming expression levels to z-scores and ordering rows and columns by complete linkage hierarchical clustering. Ingenuity pathway analysis was applied to all probesets with p≤0.01 to identify pathways significantly correlated with IC50. Additional MTT assays were initiated to test sensitivity to agents targeting these pathways. Even though most cases in all 4 groups were sensitive to obatoclax as indicated by IC50s within a clinically achievable range, MLL translocation status still had a significant effect on IC50. MLL-AF4+ cases were least sensitive and MLL-ENL+ cases were most sensitive to obatoclax. Respective IC50 ranges across all 54 cases were: MLL-AF4+, 26–918 nM; MLL-ENL+, 13–294 nM; other MLL+ 10–356 nM; MLL−, 31–488. Compared to MLL-AF4+, the IC50s in MLL-ENL+ cases were significantly lower (p=0.047), IC50s in other MLL+ cases were lower but the difference did not achieve significance (p=0.10), and IC50s in MLL- cases were not significantly different (p=0.64). In the 47 COG P9407 cases studied by MTT assay and gene expression profiling, 450 probesets defined a cluster of 16 cases with higher IC50s, which were predominantly MLL-AF4+ (68.7%). Ingenuity analysis identified significant correlations of the following canonical pathways with the IC50 in the same 47 cases: glycolysis/gluconeogenesis, mTOR signaling, regulation of eIF4 and p70S6K signaling, EIF2 signaling, and fructose and mannose metabolism. In preliminary analyses, cell lines with t(4;11) exhibited time and dose-dependant sensitivity to the eIF4e inhibitor ribavirin. In infant ALL, obatoclax has broad-spectrum activity and there is pan-sensitivity across MLL translocation subtypes and MLL− cases. Still specific MLL partner genes have a strong effect on obatoclax IC50 and there is exquisite sensitivity in MLL-ENL+ cases. This result is important because MLL-ENL is associated with particularly poor survival when conventional therapies are used. The association of differentially expressed genes in canonical cell signaling and metabolism pathways with differences in obatoclax sensitivity forms the basis to combine obatoclax with targeted agents directed at restoring these pathways to enhance responsiveness even further. Felix:None: Patent not licensed.